Sistem Informasi Objek Pajak Bumi Dan Bangunan Sektor Pedesaan Dan Perkotaan Pada Badan Pengelola Pendapatan Daerah Kabupaten Asahan - Zufria, Ilka; Harahap, Aninda Muliani; Wardani, Dina Ayu (STIKOM Tunas Bangsa Pematangsiantar, 2022)
The Regional Revenue Management Agency (BAPPENDA) of Asahan Regency in the distribution of Tax Returns Payable (SPPT) until the process of paying off Land and Building Taxes in the Rural and Urban sectors (PBB P2) to obtaining a Deposit Receipt (STTS) as proof that PBB P2 has been paid off is still not complete. efficient in terms of time. Researchers try to solve problems that occur by implementing an Information System in the process of paying off PBB P2. The results of this study are the system built at the Regional Revenue Management Agency (BAPPENDA) of Asahan Regency using the Short Message Service (SMS) Gateway in terms of commemorating the due date and using the Midtrans Payment Gateway payment method, this provides benefits to agencies in managing PBB P2 data and provide benefits for taxpayers in the process of repayment and obtain STTS so that it is more effective and efficient